REPRESENTASI NILAI NASIONALISME DALAM KARYA FILM PENDEK “NDUDAH KIDUNGE SIMBAH” - antok hermawan; Moch. Ichdah Asyarin Hayau Lailin (PAWITRA KOMUNIKA : Jurnal Komunikasi dan Sosial Humaniora, 2024)
Local films can serve as an effective means of communicating messages, especially in terms of encouraging the spirit of nationalism in the younger generation. One of them is by using short films as a medium. This research takes the object of a short film entitled "Ndudah Kidunge Simbah". The theme presented in this movie brings relevant social issues in society. The uniqueness of this film makes it an interesting object to study, because there is a communication message that the director wants to convey through this work, namely the importance of cultivating the spirit of nationalism to the younger generation The purpose of this study is to determine the representation of the value of nationalism in the short film ndudah kidunge simbah. The type of research used is descriptive qualitative research, using the content analysis method. The results showed that in several scenes of the movie Ndudah Kidunge Simbah, there is a representation of the spirit of nationalism. The message or symbol of nationalism in this film is represented by the red and white flag, national songs and the preservation of regional arts, namely kethoprak. The conclusion of this research is that Indonesian films have great potential as an effective tool to strengthen the spirit of nationalism and build awareness of national identity in the midst of cultural diversity.